Amour, sexualité et beauté chez Platon : le leçon de diotime (Banquet, 201D -212C) - Follon, Jacques (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Filosofía., 2002)
The author analyses the Sócrates’ speech in the Banquet where is explained the nature of Eros. This paper shows how Plato afflrm the unity of the deslre that means a kind of surpass of dualism and, on the other hand, his sex’s conception as ordered to the procreation and, consequently, the condemnation of the carnal homosexuality.